Bulgarian New Ageism and Civic-Religious Ideology (Religious dialogue and cooperation, 2026)
The politicization of theology and religion, on one hand, and the “theologization” of politics, on the other, are fundamental characteristics of the relationship between religion and globalization. Globalization enhances, at least in the short term, religion, and religiosity. In this way, globally oriented religions are integrated into the global political discourse on the world order as a competing ideology, whose authority significantly surpasses that of the political and economic system. Globalization raises questions about the new forms, functions, and roles of religious ideologies in the global space.A global religion example is New Age, while a new form example is civil religion. This paper would try to answer the question of whether Bulgarian New Age could shape a civil-religious ideology, whose messages, symbols, and rituals could support the moral integration of (part of) Bulgarian society. Especially in the perspective of Peter Berger, according to whom historically, in Orthodox societies, churches have never functioned as voluntary associations based on the conscious choice of believers, unlike Protestant ones.The analysis indicates that the Bulgarian New Ageism activates followers towards beneficial for society activities. The messages express the historical memory for right and wrong, that is, the reproduction of sacred traditions regardless of specific confessions. They are associated with a revivalist spiritual movement, a consequence of social crisis, uniting people under an ideological banner and missionary vision. They call for moral integration in society, including agnostics and atheists.
Keywords: Bulgarian New Ageism; civic religion